Recent advances and spectroscopic perspectives in fluoride removal. Issue 3 (16th March 2017) - Dhillon, Ankita; Prasad, Surendra; Kumar, Dinesh
ABSTRACT: With the constant rising demand for pure water to meet the needs of the growing population particularly in developing countries, fluoride remediation from drinking water has emerged as an increasingly important matter of public concern. In the past decade, significant efforts and advances have been made for developing efficient adsorbents for fluoride removal from water. This review summarizes recent advances (2012–2016) in defluoridation techniques and highlights the challenges and opportunities for future research in the important field of fluoride removal. The spectroscopic techniques, used to develop adsorbents/adsorption mechanism, discussed in this review are X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, inductively coupled plasma mass spectrometry, atomic absorption spectrometry, inductive coupled plasma-optical emission spectroscopy, and X-ray photoelectron spectroscopy. The defluoridation techniques have been discussed in four categories: precipitation, membrane, ion-exchange, and adsorption techniques. Then recent research on fluoride removal using various adsorbents with their spectroscopic studies are summarized and discussed with regard to their synthetic chemistry, properties, and applications. The advantages and disadvantages of defluoridation techniques and adsorbents have been presented. Finally, the future needs and perspectives of fluoride removal are addressed.